PENDAMPINGAN PENANAMAN BENIH, BIBIT SAYURAN DAN PEMBUKUAN PADA KELOMPOK WANITA TANI (KWT) SEKAR AYU DI BANJAR KEMENUH KELOD DESA KEMENUH KECAMATAN SUKAWATI KABUPATEN GIANYAR - Ni Luh Gede Sudaryati; Suparmi Suparmi; Ni Made Listya Ari; Ni Wayan Ariska Yustina (UNHI Press, 2021)
Food security is access by all at all times to sufficient food for a healthy and active life. The nutritional status of the community is determined by food consumption and the body's ability to use nutrients. The COVID-19 pandemic that has been running for more than 1 year has an impact not only on health but also on the economy and food, causing people to have limited access to nutritious food. Women Farmers Group is a form of farmer group whose members consist of women who are involved in agricultural activities, in the implementation of activities directed at empowering household-scale agricultural businesses in order to increase family income. The problems experienced by the Sekar Ayu Women Farmers Group (KWT) at this time are that they do not know about food and nutrition sources which can be produced from their own yards, do not have to buy and how to prepare good books so they cannot know for sure how many vegetable seeds they need. planted, distributed to members, how much expenses and yields. Based on the background of the problems of the Women Farmers Group (KWT) Sekar Ayu, the solutions that can be offered in community service are assistance on food counseling, nutrition and the preparation of administrative books. The purpose of this community service program is to provide knowledge to the women farmer group (KWT) Sekar Ayu about food sources, nutrition and provide training in the preparation of administrative bookkeeping so that it is easy to control and report activities to the local government. The implementation method used is food counseling, nutrition and administrative bookkeeping training. From the results of mentoring activities for planting seeds, vegetable seeds and bookkeeping training for members of the Sekar Ayu women farmer group (KWT) it can be concluded that through this activity will add added value and positive benefits in planting seeds, vegetable seeds and bookkeeping training, especially members of the women farmer group ( KWT) can increase crop yields and make it easier to report activities